Extracellular Vesicle-Contained microRNA of C. elegans as a Tool to Decipher the Molecular Basis of Nematode Parasitism - Duguet, Thomas B.; Soichot, Julien; Kuzyakiv, Rostyslav; Malmström, Lars; Tritten, Lucienne (Frontiers in Cellular and Infection Microbiology, 2020)
Among the fundamental biological processes affected by microRNAs, small regulators of gene expression, a potential role in host-parasite communication is intriguing. We compared the miRNA complement of extracellular vesicles released by the free-living nematode Caenorhabditis elegans in culture to that of other adult parasitic nematodes. Expecting convergent functional roles for secreted miRNAs due to the common parasitic life-style of the organisms under investigation, we performed a miRNA sequence analysis as well as target search and pathway enrichment for potential mRNA targets within host immune functions. We found that the parasite miRNA seed sequences were more often identical to those of C. elegans, rather than to those of their hosts. However, we observed that the nematode-secreted miRNA fractions shared more often seed sequences with host miRNAs than those that are not found in the extracellular environment. Development and proliferation of immune cells was predicted to be affected several-fold by nematode miRNA release. In addition, we identified the AGE-RAGE signaling as a convergent targeted pathway by species-specific miRNAs from several parasitic species. We propose a multi-species comparative approach to differentiate those miRNAs that may have critical functions in host modulation, from those that may not. With our straight-forward analysis, we put forward a workflow to study traits of parasitism at the miRNA level. This work will find even more resonance and significance, as an increasing amount of parasite miRNA collections will be produced in the future.